PEMBINAAN MINAT WIRAUSAHA BERBASIS GREEN BUSINESS BAGI MASYARAKAT - Pradana, Bayu Ilham; Parwati, Kardina Yudha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The phenomenon of green business has the potential to contribute to the local economy if provided with appropriate guidance and support throughout the process. The city of Malang has a climate and environment conducive to the development of green businesses by utilizing natural resources. Efforts to enhance interest in environmentally friendly and sustainable entrepreneurship through green business programs can be seen from affective, cognitive, and conative perspectives. These activities contribute to the implementation of the Green Business concept, especially in increasing the economic value of plant cultivation, thereby benefiting the local community's economy. Initiatives to develop interest in entrepreneurship based on green business are carried out in the Mojolangu Village, Lowokwaru Sub-district, Malang City, in collaboration with the agribusiness company Semi Abadi and the Karang Taruna community organization of Mojolangu Village, involving a total of 28 participants. The results of these activities include an increased interest in green business entrepreneurship as assessed from the affective, cognitive, and conative aspects among the training participants. The sustainability of the results of the community service evaluation can be followed up by providing assistance in the preparation of a business plan, training in product packaging, digital marketing training, and financial management training for succulent plant business products. Additionally, it can also include mentoring for green business-based succulent plant enterprises that are already in operation. Abstrak Fenomena green business memiliki potensi untuk memberikan kontribusi pada perekonomian lokal jika mendapat panduan dan dukungan yang tepat selama prosesnya. Kota Malang memiliki iklim dan lingkungan yang mendukung untuk pengembangan green business dengan memanfaatkan media yang bersumber dari alam. Usaha meningkatkan minat wirausaha yang ramah lingkungan dan berkelanjutan melalui program green business dapat dilihat dari sisi afektif, kognitif dan konatif. Kegiatan ini berkontribusi dalam implementasi konsep Green Business terutama dalam peningkatan nilai ekonomis dari budidaya tanaman sehingga memberikan manfaat pada perekonomian masyarakat setempat. Inisiatif untuk mengembangkan minat berwirausaha berbasis green business dilaksanakan di Kelurahan Mojolangu, Kecamatan Lowokwaru, Kota Malang, bekerja sama dengan usaha agribisnis Semi Abadi dan mitra Karang Taruna Kelurahan Mojolangu dengan jumlah peserta 28 orang. Hasil dari kegiatan ini adalah meningkatnya minat wirausaha green business ditinjau dari sisi afektif, kognitif dan konatif bagi peserta pelatihan. Keberlanjutan hasil evaluasi pengabdian dapat ditindaklanjuti dengan melakukan pendampingan penyusunan business plan, pelatihan pengemasan produk, pelatihan digital marketing, dan pelatihan pengelolaan keuangan untuk produk usaha tanaman sukulen, serta dapat juga dilaksanakan pembinaan usaha berbasis green business tanaman sukulen yang telah berjalan.